PEMANFAATAN LIMBAH KULIT SINGKONG UNTUK PRODUKSI ENERGI LISTRIK MENGGUNAKAN RANGKAIAN JOULE THIEF DENGAN TEKNOLOGI MICROBIAL FUELL CELL (PENAMBAHAN RAGI DAN ASETAT) - Situmorang, Elfrina; Supriyanto, Amir; Surtono, Arif; Junaidi, Junaidi (Journal of Energy, Material, and Instrumentation Technology, 2024)
The Cassava peel waste can be used as a substrate in the Microbial Fuel Cell (MFC) system to produce electrical energy. MFC was made of acrylic with a size of 9×9×11 cm with a dual chamber type that can accommodate a substrate volume of ±350 ml. The MFC system consists of 10 cells arranged in series with voltage and current measurements every 2 hours for 72 hours using a multimeter. The maximum power MFC produces by adding 16 ml of acetate using a joule thief amplifier circuit is 8.42 W. In contrast, the addition of 24 gr yeast produces a maximum power of 7.82 W; without any addition, it produces 7.74 W of power. The amplifier also produces pretty good power. The maximum power produced by MFC without an amplifier circuit with the addition of 24 gr yeast is 2.51 mW, while 16 acetate is 2.18 mW. Without any addition, it produces 1.91 mW of power.